Interpreting locomotor biomechanics from the morphology of human footprints. Issue 90 (January 2016) - Hatala, Kevin G.; Wunderlich, Roshna E.; Dingwall, Heather L.; Richmond, Brian G.
Abstract: Fossil hominin footprints offer unique direct windows to the locomotor behaviors of our ancestors. These data could allow a clearer understanding of the evolution of human locomotion by circumventing issues associated with indirect interpretations of habitual locomotor patterns from fossil skeletal material. However, before we can use fossil hominin footprints to understand better the evolution of human locomotion, we must first develop an understanding of how locomotor biomechanics are preserved in, and can be inferred from, footprint morphologies. In this experimental study, 41 habitually barefoot modern humans created footprints under controlled conditions in which variables related to locomotor biomechanics could be quantified. Measurements of regional topography (depth) were taken from 3D models of those footprints, and principal components analysis was used to identify orthogonal axes that described the largest proportions of topographic variance within the human experimental sample. Linear mixed effects models were used to quantify the influences of biomechanical variables on the first five principal axes of footprint topographic variation, thus providing new information on the biomechanical variables most evidently expressed in the morphology of human footprints. The footprint's overall depth was considered as a confounding variable, since biomechanics may be linked to the extent to which a substrate deforms. Three of five axes showed statistically significant relationships with variables related to both locomotor biomechanics and substrate displacement; one axis was influenced only by biomechanics and another only by the overall depth of the footprint. Principal axes of footprint morphological variation were significantly related to gait type (walking or running), kinematics of the hip and ankle joints and the distribution of pressure beneath the foot. These results provide the first quantitative framework for developing hypotheses regarding the biomechanical patterns reflected by fossil hominin footprints by demonstrating the statistically significant effects of specific kinematic variables on patterns of variation in footprint topography.